The Effectiveness of the Jamsostek Mobile (JMO) Application among Company Workers in the Working Area of Musi Rawas Regency: Efektivitas Aplikasi Jamsostek Mobile (JMO) Pada Pekerja Perusahaan Di Wilayah Kerja Kabupaten Musi Rawas - Nova Apriza Cahyani; Henny Aprianty; Rahiman Dani (Gayaku Publisher, 2025)
This study aims to analyze the effectiveness of the use of the Jamsostek Mobile (JMO) application and to identify strategies for facilitating its use among company workers in the working area of Musi Rawas Regency. This research employed a qualitative descriptive approach. The informants consisted of five individuals selected through purposive sampling. The results indicate that the effectiveness of the Jamsostek Mobile (JMO) application can be categorized as fairly effective. This is reflected in the clarity of program objectives that have been well understood by users, the existence of planning that supports service digitalization, the availability of supporting facilities and infrastructure, although not yet evenly distributed, and the implementation of the program that has provided convenience and efficiency in services for workers. However, improvements are still needed in internet network infrastructure, electricity supply stability, as well as digital socialization and education for workers to further optimize the effectiveness of JMO usage. The main strategies to facilitate the use of the JMO application include enhancing education and socialization programs for workers, providing assistance through companies, improving internet network infrastructure, simplifying the application system, enhancing service quality, and strengthening collaboration among BPJS Ketenagakerjaan, companies, local government, and workers.